2006
DOI: 10.1149/1.2356155
|View full text |Cite
|
Sign up to set email alerts
|

64-Electrode PEM Fuel Cell Studies of CO-Tolerant Hydrogen Oxidation Catalysts

Abstract: The hydrogen oxidation catalytic performance of a ternary composition spread (Pt1-xRux)1-yMoy sample has been determined in a 64-electrode proton exchange membrane fuel cell. Linear gradients of the three elements were sputter deposited onto 3M's nano-structured thin film support through a shadow mask to produce 64 different, electrically isolated, catalyst compositions. CO stripping voltammetry showed that pre-adsorbed CO was removed at lower potentials as the ruthenium content increased. The presence of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Significant work on CO as a fuel cell impurity is the result of its ubiquitous presence, often at high concentrations, in the effluent from hydrocarbon reforming processes. These CO fuel cell studies have looked at many aspects of CO poisoning: examining CO performance effects in fuel cells, , modeling CO effects on fuel cell operation, developing operational methods to minimize CO poisoning in fuel cells, developing anodes more tolerant to CO, and making fundamental electrocatalytic measurements of CO with electrocatalysts. ,,, These studies have shown that CO forms a strong bond with Pt, chemisorbing on the metal surface. The chemisorbed CO blocks the adsorption of hydrogen onto active Pt sites for hydrogen electro-oxidation (HOR).…”
Section: 11 Fuel Impuritiesmentioning
confidence: 99%
“…Significant work on CO as a fuel cell impurity is the result of its ubiquitous presence, often at high concentrations, in the effluent from hydrocarbon reforming processes. These CO fuel cell studies have looked at many aspects of CO poisoning: examining CO performance effects in fuel cells, , modeling CO effects on fuel cell operation, developing operational methods to minimize CO poisoning in fuel cells, developing anodes more tolerant to CO, and making fundamental electrocatalytic measurements of CO with electrocatalysts. ,,, These studies have shown that CO forms a strong bond with Pt, chemisorbing on the metal surface. The chemisorbed CO blocks the adsorption of hydrogen onto active Pt sites for hydrogen electro-oxidation (HOR).…”
Section: 11 Fuel Impuritiesmentioning
confidence: 99%
“…The third category [20][21][22][23] pertains most closely to the nature of the NSTF catalyst structure. The largest group of publications [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] is related to the NSTF catalyst electrochemical characteristics, from fundamental RDE measurements of unique alloys and compositional spreads, to activity and surface area characterizations in 50 cm 2 MEA fuel cells. References 39,40 relate to the vacuum coating processes for NSTF fabrication.…”
Section: Organization Of the Nstf Literaturementioning
confidence: 99%